2022
DOI: 10.3389/fphar.2022.811422
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Potential Target of Blood-Activating Chinese Botanical Drugs Combined With Anti-Platelet Drugs: Prevention and Treatment of Atherosclerotic Cardiovascular Diseases

Abstract: Atherosclerotic cardiovascular diseases (ASCVDs) are the most important diseases that endanger people’s health, leading to high morbidity and mortality worldwide. In addition, various thrombotic events secondary to cardiovascular and cerebrovascular diseases need must be considered seriously. Therefore, the development of novel anti-platelet drugs with high efficiency, and fewer adverse effects has become a research focus for preventing of cardiovascular diseases (CVDs). Blood-activation and stasis-removal fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 124 publications
0
7
0
Order By: Relevance
“…Several studies have shown that herbal extracts can be used in combination with antithrombotic drugs to enhance efficacy and clinical safety (Li, Li, et al, 2022). Some natural products have exhibited the same properties, such as epigallocatechin‐3‐gallate, which in combination with warfarin was able to reduce deep venous thrombosis (Li, Ge, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that herbal extracts can be used in combination with antithrombotic drugs to enhance efficacy and clinical safety (Li, Li, et al, 2022). Some natural products have exhibited the same properties, such as epigallocatechin‐3‐gallate, which in combination with warfarin was able to reduce deep venous thrombosis (Li, Ge, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, the presence of blood stasis obstructs the veins, thereby exacerbating the hindrance of both Qi and blood flow, ultimately culminating in the progression of atherosclerosis ( Li et al, 2024 ). Hence, traditional Chinese medical practitioners have endeavored to enhance the flow of blood in order to eliminate pathogenic toxins within the vessels, a practice referred to as “promote blood circulation and remove blood stasis.” This principle has emerged as a crucial strategy for treating atherosclerosis within the system of TCM ( Li et al, 2022 ). Interestingly, DS has been found to enhance hemodynamic circulation and promote tissue regeneration, whereas ancient texts suggest that the effectiveness of DS is comparable to Si Wu Tang, indicating its potential for the blood-activating and stasis-resolving properties equivalent to the combination of Radix Angelicae Sinensis , Radix Paeoniae Alba , Rhizoma Ligustici Wallichii , and Rhizoma Rehmanniae ( Yang and Ma, 2024 ).…”
Section: Ethnopharmacological Relevancementioning
confidence: 99%
“…This formula has the effect of nourishing yin and the blood. [113] The study have showed that Huoxue Rongluo Decoction alleviates CIRI by down-regulating miR-370-3p, activating the expression of JAK2/STAT3 pathway, increasing downstream VEGF, enhancing microvascular density in the ischemic area, and improving the degree of cerebral vascular neovascularization. [114,115] In addition to the TCM herbal compound mentioned above, studies have shown that Sijunzi Decoction and Yupingfeng Powder could also regulating the level of JAK and STAT to influence the expression of inflammatory factors including IL-4.…”
Section: Buyang Huanwu Decoctionmentioning
confidence: 99%